2020
DOI: 10.1016/j.heliyon.2020.e04710
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of bergapten in acetic acid-induced colitis in rats

Abstract: Bergapten (5-methoxysporalen) is a furanocoumarin extracted from several species of citrus and bergamot oil. Bergamot essential oil is used traditionally in the management of inflammatory conditions. Previous studies on bergapten have explored mainly its in vitro anti-inflammatory activities which include suppression of the expression and release of pro-inflammatory cytokines such as TNF-α and interleukins as well as prostaglandins. Bergapten enhances the clearance of neutrophils and mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…In another study, the anti-inflammatory effects of BP were investigated in a rat model of acetic acid-induced colitis [ 34 ]. Oral administration of BP (3, 10, and 30 mg/kg) normalized colon weight-to-length and significantly reduced tissue damage and the number of degranulated mast cells.…”
Section: Pharmacological Activities Of Bergapten: Preclinical Evidenc...mentioning
confidence: 99%
“…In another study, the anti-inflammatory effects of BP were investigated in a rat model of acetic acid-induced colitis [ 34 ]. Oral administration of BP (3, 10, and 30 mg/kg) normalized colon weight-to-length and significantly reduced tissue damage and the number of degranulated mast cells.…”
Section: Pharmacological Activities Of Bergapten: Preclinical Evidenc...mentioning
confidence: 99%
“…Bergapten (5-methoxypsoralen), a furocoumarin found in medicinal plants, has become a compound of considerable interest in current research [ 16 , 17 ]. Accumulated reports have demonstrated the potential therapeutic effects of bergapten in various disease conditions including psoriasis and vitiligo [ 18 , 19 ], Alzheimer's disease (AD) [ 20 ], depression [ 21 ], osteoporosis [ 22 ], cancer [ 23 ], colitis [ 24 ], and asthma [ 25 ]. Prior in vitro studies on human peripheral blood mononuclear cells (PBMCs) showed that bergapten could suppress the release of lipopolysaccharide- (LPS-) stimulated proinflammatory cytokines such as tumour necrosis factor-alpha (TNF- α ) and interleukin 6 (IL-6) production [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macroscopic changes in colon related to acetic acid include thickening of intestinal walls, ulceration, and necrosis. Mucosal lining damage, necrosis of tissues with hemorrhages, goblet cells loss, and infiltration of inflammatory cells have been reported in histopathological examination of colitis 12 , 13 , 28 . Biochemical results revealed significant increase in inflammatory cytokines IL-1β, TNF-α, IL-6 and also decrease in IL-10 29 .…”
Section: Discussionmentioning
confidence: 99%